Effectiveness of Collaborative Governance Management of Public Complaints Based on Electronic Communication Media In Central Java Provincial Government - Widianto, Dhoni; Pujiono, Pujiono; Astuti, Retno Sunu; Wijayanto, Wijayanto (Budapest International Research and Critics University, 2021)
This study aims to describe the effectiveness of Collaborative Governance in managing public complaints based on electronic communication media in the Central Java Provincial Government for 3 (three years, 2017, 2018, and 2019. This research method uses descriptive qualitative methods. The location of this research is in the Central Java Provincial Government conducted at the Department of Communication and Informatics of Central Java Province. The results of the study conclude that this collaboration has not been effective, such as the lack of commitment from other stakeholders outside the Central Java Provincial SKPD such as Regency/City Governments, vertical agencies, BUMN, and BUMD. Then the limited authority of the Provincial Government of Java Central to the Regency/City Government, vertical agencies, BUMN, and BUMD, resulting in the completion of follow-up on community complaints is still low.The governance of handling public complaints by stakeholders is unclear, lack of accountability and responsibility from stakeholders other than S. KPD of Central Java Province and the supervisory team has not yet been formed to control the follow-up to the handling of complaints in the field.